Transcriptomic analysis of three Veillonella spp. present in carious dentine and in the saliva of caries-free individuals - Do, Thuy; Sheehy, Evelyn C.; Mulli, Tonnie; Hughes, Francis; Beighton, David (Frontiers in Cellular and Infection Microbiology, 2015)
Veillonella spp. are predominant bacteria found in all oral biofilms. In this study, a metatranscriptomic approach was used to investigate the gene expression levels of three oral Veillonella spp. (V. parvula, V. dispar and V. atypica) in whole stimulated saliva from caries-free volunteers and in carious lesions (n = 11 for each group). In the lesions the greatest proportion of reads were assigned to V. parvula and genes with the highest level of expression in carious samples were those coding for membrane transport systems. All three Veillonella spp. increased expression of genes involved in the catabolism of lactate and succinate, notably the alpha- and beta-subunits of L(+)-tartrate dehydratase (EC 4.2.1.32). There was also significantly increased expression of histidine biosynthesis pathway in V. parvula, suggesting higher intra-cellular levels of histidine that could provide intra-cellular buffering capacity and, therefore, assist survival in the acidic environment. Various other systems such as potassium uptake systems were also up regulated that may aid in the survival and proliferation of V. parvula in carious lesions.